High-dose-rate intraluminal brachytherapy prior to external radiochemotherapy in locally advanced esophageal cancer: preliminary results - Safaei, Afsaneh Maddah; Ghalehtaki, Reza; Khanjani, Nezhat; Farazmand, Borna; Babaei, Mohammad; Esmati, Ebrahim (Journal of Contemporary Brachytherapy, 2017)
Purpose: Dysphagia is a common initial presentation in locally advanced esophageal cancer and negatively impacts patient quality of life and treatment compliance. To induce fast relief of dysphagia in patients with potentially operable esophageal cancer high-dose-rate (HDR) brachytherapy was applied prior to definitive radiochemotherapy. Material and methods : In this single arm phase II clinical trial between 2013 to 2014 twenty patients with locally advanced esophageal cancer (17 squamous cell and 3 adenocarcinoma) were treated with upfront 10 Gy HDR brachytherapy, followed by 50.4 Gy external beam radiotherapy (EBRT) and concurrent chemotherapy with cisplatin/5-fluorouracil. Results : Tumor response, as measured by endoscopy and/or computed tomography scan, revealed complete remission in 16 and partial response in 4 patients (overall response rate 100%). Improvement of dysphagia was induced by brachytherapy within a few days and maintained up to the end of treatment in 80% of patients. No differences in either response rate or dysphagia resolution were found between squamous cell and adenocarcinoma histology. The grade 2 and 3 acute pancytopenia or bicytopenia reported in 4 patients, while sub-acute adverse effects with painful ulceration was seen in five patients, occurring after a median of 2 months. A perforation developed in one patient during the procedure of brachytherapy that resolved successfully with immediate surgery. Conclusions : Brachytherapy before EBRT was a safe and effective procedure to induce rapid and durable relief from dysphagia, especially when combined with EBRT.